The unintended consequence of SO2 and NO2 regulations over China: increase of ammonia levels and impact on PM2.5 concentrations - M. Lachatre; A. Fortems-Cheiney; A. Fortems-Cheiney; G. Foret; G. Siour; G. Dufour; L. Clarisse; C. Clerbaux; C. Clerbaux; P.-F. Coheur; M. Van Damme; M. Beekmann (Atmospheric Chemistry and Physics, 2019)
Air pollution reaching hazardous levels in many Chinese cities has been a major concern in China over the past decades. New policies have been applied to regulate anthropogenic pollutant emissions, leading to changes in atmospheric composition and in particulate matter (PM) production. Increasing levels of atmospheric ammonia columns have been observed by satellite during recent years. In particular, observations from the Infrared Atmospheric Sounding Interferometer (IASI) reveal an increase of these columns by 15 % and 65 % from 2011 to 2013 and 2015, respectively, over eastern China. In this paper we performed model simulations for 2011, 2013 and 2015 in order to understand the origin of this increase and to quantify the link between ammonia and the inorganic components of particles: <msubsup>NH4(p)+</msubsup>/<msubsup>SO4(p)2-</msubsup>/<msubsup>NO3(p)-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="106pt" height="19pt" class="svg-formula" dspmath="mathimg" md5hash="383a7405c287bf607266d5c594614af7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-6701-2019-ie00001.svg" width="106pt" height="19pt" src="acp-19-6701-2019-ie00001.png"/></svg:svg>. Interannual change of meteorology can be excluded as a reason: year 2015 meteorology leads to enhanced sulfate production over eastern China, which increases the ammonium and decreases the ammonia content, which is contrary to satellite observations. Reductions in SO2 and NOx emissions from 2011 to 2015 of 37.5 % and 21 % respectively, as constrained from satellite data, lead to decreased inorganic matter (by 14 % for <msubsup>NH4(p)+</msubsup>+<msubsup>SO4(p)2-</msubsup>+<msubsup>NO3(p)-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="116pt" height="19pt" class="svg-formula" dspmath="mathimg" md5hash="6b6ac4fbd711028cde370280ca4c77d5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-19-6701-2019-ie00002.svg" width="116pt" height="19pt" src="acp-19-6701-2019-ie00002.png"/></svg:svg>). This in turn leads to increased gaseous NH3(g) tropospheric columns by as much as 24 % and 49 % (sampled corresponding to IASI data availability) from 2011 to 2013 and 2015 respectively and thus can explain most of the observed increase.